Feasibility study for future contributions in the field of forest biodiversity assessments - Richard Fischer (Federal Research Centre for Forestry and Forest Products (BFH), Institute for World Forestry, 2003)
As a basis of the ICP Forests feasibility study this overview describes national activities in the field of forest biodiversity monitoring. It takes into account 15 participating countries of ICP Forests, including those that already in 2002 were interested in a participation in an ICP Forests biodiversity test-phase and those that had already submitted relevant reports to the to the Convention on Biological Diversity (CBD). Results show that the importance of forest biodiversity and related monitoring has been recognized in most countries. The evaluated countries differ widely in the extent of implemented national biodiversity monitoring programmes. A first evaluation of National Forest Inventory methodologies shows that stand structural information should be available from most inventories - although not in an harmonized format, whereas information on compositional aspects of forest biodiversity, e.g. in the form of ground vegetation species lists, is hardly available from existing national forest inventories.
urn:nbn:de:gbv:253-200912-dk040081-4
Keywords: 630